Incorporating Virtual Reality to Improve Otolaryngology Resident Wellness: One Institution's Experience. (25th March 2021) - Weitzman, Rachel E.; Wong, Kevin; Worrall, Douglas M.; Park, Christopher; McKee, Sean; Tufts, Ryan E.; Teng, Marita S.; Iloreta, Alfred M.
Abstract : Objective: Burnout is defined as work‐related emotional exhaustion, depersonalization, and decreased sense of accomplishment. Virtual reality (VR) has emerged as an effective treatment modality for various conditions related to anxiety, however, few studies have assessed its role for stress management in residents. We hypothesize that VR‐based mindfulness meditation can reduce resident burnout in real‐world settings. Study Design: Prospective randomized crossover trial. Methods: Resident participants completed the validated Maslach Burnout Inventory (MBI). One group used a VR‐based meditation app; the second group received no intervention. After a 2‐month rotation, all subjects completed an MBI and crossed over to the other arm. Wilcoxon rank‐sum tests were used to compare MBI scores before and after intervention, and to compare results by gender and postgraduate year. Mann‐Whitney U tests were used to assess qualitative differences between participants. Results: Eighteen residents completed the study. Five participants were female and 13 were male. Weekly use of VR‐guided meditation and paced breathing was associated with a significant decrease in emotional exhaustion ( P = .009), and on subgroup analysis, male gender specifically was associated with a decrease in emotional exhaustion ( P = .027). In the post‐intervention survey, 42.9% subjects reported that VR encouraged them to employ paced breathing techniques, 71.4% reported that they would use the technology if regularly available, and 21.4% reported they would use paced breathing in the future. Conclusion: VR‐based therapy may serve as a successful tool in stress management and reduce the rate of burnout among otolaryngology residents. Level of Evidence: NA Laryngoscope, 131:1972–1976, 2021